Disruption to normal excitatory and inhibitory function within the medial prefrontal cortex in people with chronic pain. (26th July 2021) - Kang, David; Hesam‐Shariati, Negin; McAuley, James H.; Alam, Monzurul; Trost, Zina; Rae, Caroline D.; Gustin, Sylvia M.
Abstract: Background: Growing evidence indicates a link between changes in the medial prefrontal cortex and the pathophysiology of chronic pain. In particular, chronic pain is associated with altered medial prefrontal anatomy and biochemistry. Due to the comorbid affective disorders seen across all pain conditions, the medial prefrontal cortex is a region of significance as it is involved in emotional processing. We have recently reported that a decrease in medial prefrontal N ‐acetylaspartate and glutamate is associated with increased emotional dysregulation, indicating there are neurotransmitter imbalances in chronic pain. Therefore, we compared medial prefrontal neurochemistry in 24 people with chronic pain conditions to 24 age and sex‐matched healthy controls with no history of chronic pain. Method: GABA‐edited MEGA‐PRESS was used to measure GABA + levels, and short TE PRESS was used to measure glutamate levels in the medial prefrontal cortex. Psychometric measures regarding pain intensity a week before scanning, during the scan and the total duration of chronic pain, were also recorded and compared to measured GABA + and glutamate levels. Results: This study reveals that the presence of chronic pain is associated with significant decreases in medial prefrontal GABA + and glutamate. These findings support the hypothesis that chronic pain is associated with altered medial prefrontal biochemistry. Conclusion: The dysregulation of glutamatergic and GABAergic neurotransmitter systems supports a model of disinhibition of chronic pain, which may play a key role in both the experience of persistent pain and its associated affective disturbances. Significance: This study reveals a significant reduction in γ‐aminobutyric acid (GABA + ) and glutamate within the medial prefrontal cortex in chronic pain sufferers. While the current findings should be considered with reference to a small sample size, the disruption to normal excitatory and inhibitory medial prefrontal cortex function may be key in the development and maintenance of chronic pain and comorbid mental health disorders.